Performance of fibre reinforced, low density metakaolin geopolymers under simulated fire conditions - Rickard, William; Vickers, Les; Van Riessen, Arie (Elsevier BV, 2013)
This paper presents a study on the thermal behaviour of metakaolin based geopolymers that have been foamed and fibre reinforced in order t1o assess their suitability for high temperature applications such as thermal barriers and fire resistant panels. An international standard fire curve (ISO 834, 1999) was used to simulate the heating conditions of a fire. Fire testing was conducted on 50 mm thick panels with an exposure size of 200 mm×200 mm. Fire ratings of more than one hour were achieved for all samples.